Caries Prevention Effects of Nano Silver Fluoride Sustained Release Orthodontic Elastomerics in Dental Microcosm Biofilms - R Mhaske, Arun; Kamalkishor Fafat, kapil; Khan, Waseem; Dnyandeo Tekale, Pawankumar; Mohd Altaf Qureshi Mohd Ilyas Qureshi, Chaudhari; Rehman Foujdar, Abdul (Journal of Neonatal Surgery, 2025)
Dental caries remains one of the most prevalent oral health concerns, particularly among orthodontic patients who are at an increased risk due to the presence of fixed appliances such as brackets and elastomeric ligatures. These orthodontic materials provide additional surfaces for bacterial adhesion, contributing to the formation of biofilms that harbor acid-producing microorganisms. The persistent accumulation of biofilms leads to demineralization of the enamel, which, if left unchecked, progresses into white spot lesions (WSLs) and eventual cavitated carious lesions. Despite the widespread use of fluoride-releasing materials and antimicrobial agents, their efficacy is often compromised by factors such as short-term bioavailability, bacterial resistance, and adverse side effects, including oral dysbiosis and staining. Given these limitations, there is an urgent need for novel preventive strategies that provide sustained antibacterial action while promoting enamel remineralization. The objective of this study is to evaluate the clinical applicability of nano silver fluoride sustained release orthodontic elastomerics (NSF-RE) in inhibiting biofilm formation and enamel demineralization in an experimental dental microcosm biofilm model that mimics real-world oral conditions (Choi et al., 2025). Unlike conventional fluoride-based treatments, NSF-RE is designed to deliver a controlled and prolonged release of antimicrobial agents, ensuring continuous protection against cariogenic bacteria. This study investigates two distinct NSF formulations—NSF-EP, which incorporates polyethylene glycol (PEG) as a plasticizer, and NSF-E, which lacks PEG. The inclusion of PEG is hypothesized to enhance the sustained release of active ingredients, thereby increasing the antimicrobial efficacy of the elastomerics. To assess the effectiveness of these formulations, orthodontic elastomeric ligatures were dip-coated with NSF and applied to enamel specimens inoculated with saliva-derived dental microcosm biofilms. Over a period of seven days, biofilm thickness, bacterial viability, and mineral loss beneath the biofilm were systematically measured to compare the antimicrobial and remineralizing effects of NSF-EP and NSF-E (Kim et al., 2021). The findings revealed that NSF-EP significantly inhibited biofilm formation, reducing thickness by 36.1% compared to uncoated elastomerics. Furthermore, the quantitative light-induced fluorescence (QLF-D) analysis demonstrated that NSF-EP led to a substantial increase in enamel remineralization, as indicated by ΔF and ΔFmax values rising by 34.8% and 38.7%, respectively (Choi et al., 2022). The results of this study highlight NSF-RE as a promising dual-function caries prevention strategy for orthodontic patients, offering both antibacterial action and fluoride-mediated remineralization. The ability of NSF-RE to sustainably release antimicrobial and remineralizing agents presents a significant advantage over traditional short-term treatments, which require frequent reapplication and exhibit diminishing effectiveness over time. By integrating nano silver fluoride technology into orthodontic materials, this study provides evidence for a clinically viable solution that could revolutionize caries prevention in orthodontic patients. Future research should focus on long-term clinical trials to further evaluate the safety, efficacy, and patient outcomes associated with the sustained use of NSF-RE in orthodontic treatments.